Pelaksanaan Layanan Konseling Individual dalam Mengatasi Nomophobia pada Siswa di SMP Negeri 1 Badar Kutacane - Mia Aulia (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The aims of this research are: 1. to describe how individual counseling services are implemented in overcoming nomophobia in students, 2. the characteristics, factors and impacts of nomophobia experienced by students at SMP Negeri 1 Badar. The type of research in this thesis uses descriptive qualitative methods. The subjects and objects in this research are the school principal, guidance and counseling teachers, and students. The research instruments are interviews, observation and documentation. The analysis consists of 3 flows, interacting data analysis techniques that reduce data, present data and draw conclusions. The research results show that: 1. Implementation of individual counseling services at SMP Negeri 1 Badar. 2. Characteristics, factors and impact of Nomophobia on students at SMP Negeri 1 Badar. The individual counseling services provided to students are tailored to the student's own needs and problems. The implementation of individual counseling services at SMP Negeri 1 Badar is carried out when students have problems that require the use of individual counseling service techniques, so that students know the impact and are able to solve the problem together with the Guidance and Counseling teacher.